Estimation of Total Solar Radiation from Latitude and Sunshine Duration - Gopinathan, K K (Annals of Arid Zone, 2016)
Correlations are suggested for calcula ting the regression coefficients a and b of equation H’ = Ho (a+b S/S’O> suggested by Hay (Solar Energy, 23, 301,1979) for global solar radiation. The proposed correlations calculate a and b constants from latitude and sunshine duration for a given station. The correlations are developed from the latitude, the reported regression parameters and sunshine duration for twelve locations spread all around India. The applicability cf the proposed equations is tested by calculating the regression coefficients and hence the global solar radiation for three new locations in India. The remarkable agreement between the measured and estimated values of global radiation suggests the wide applicability of the method for locations in Indi